Pelatihan Sumber Daya Manusia “Character Building” Posyandu Remaja Mekarmukti Kecamatan Cikarang Utara Kabupaten Bekasi - Mardiani, Inna Nisawati; Wicaksana, Primaraga Sumantri Indra; Yahya, Adibah; Windi (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Character education is efforts that are systematically designed and implemented in order to instill human behavioral values related to God Almighty, oneself, fellow human beings, the environment and nationality. The formation of the adolescent personality is related to many factors that influence it such as through education and self-control, emotional intelligence, the environment where blessings/work, conditions and self-discipline, the ability to manage oneself/emotions, the ability to face the situation at hand, and much more that can support the person. Character building is an effort to build and shape a person's morals and ethics to be good. This community service aims to develop the abilities of adolescents in an effort to build positive character. The method in this service is to provide training on Character Building to the cadres of the Mekarmukti Youth Posyandu, North Cikarang District, Bekasi Regency, which totals 51 people. The participants before and after the training were given evaluations related to understanding Character Building. After providing training on Character Building, there is an increase in knowledge about Character Building, so that participants can understand the importance of building positive character in themselves.